Analyses of the Effects of Arginine, Nicotine, Serotype and Collagen-Binding Proteins on Biofilm Development by 33 Strains of Streptococcus mutans - Wagenknecht, Dawn R.; Gregory, Richard L. (Frontiers in Oral Health, 2021)
Streptococcus mutans serotype k strains comprise <3% of oral isolates of S. mutans but are prominent in diseased cardiovascular (CV) tissue. Collagen binding protein (CBP) genes, cbm and cnm, are prevalent in serotype k strains and are associated with endothelial cell invasion. Nicotine increases biofilm formation by serotype c strains of S. mutans, but its effects on serotype k strains and strains with CBP are unknown. Saliva contains arginine which alters certain properties of the extracellular polysaccharides (EPS) in S. mutans biofilm. We examined whether nicotine and arginine affect sucrose-induced biofilm of S. mutans serotypes k (n=23) and c (n=10) strains with and without CBP genes. Biofilm mass, metabolism, bacterial proliferation, and EPS production were assessed. Nicotine increased biomass and metabolic activity (p<0.0001); arginine alone had no effect. The presence of a CBP gene (either cbm or cnm) had a significant effect on biofilm production, but serotype did not. Nicotine increased bacterial proliferation and the effect was greater in CBP+ strains compared to strains lacking CBP genes. Addition of arginine with nicotine decreased both bacterial mass and EPS compared to biofilm grown in nicotine alone. EPS production was greater in cnm+ than cbm+ strains (p<0.0001). Given the findings of S. mutans in diseased CV tissue, a nicotine induced increase in biofilm production by CBP+ strains may be a key link between tobacco use and CV diseases.